1996
DOI: 10.1021/ma951422+
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer and Electron Transfer Distances in Heteropolysilane Langmuir−Blodgett Films

Abstract: Energy transfer distances from polysilanes bearing alkyl groups to those bearing aromatic groups are estimated by employing heteropolysilane Langmuir−Blodgett (LB) films. In the heteropolysilane films, AL1-LB film (10 layers, poly((hydroxyhexyl)hexylsilane))/I1-LB film (n layers, insulator polymer, (isobutyl methacrylate))/AR1-LB film (10 layers, poly((hydroxyphenyl)butylsilane)), AL1 is selectively excited with 310 nm light and the fluorescence from AR1-LB film is observed, as the number of insulator layers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The fluorescence quenching of a monomethin-oxacyanine dye by monomethin thiacyanine was studied in the LB films, and the intermolecular energy transfer between dyes was shown to occur on a scale of 10 nm. The energy transfer distance between the two polysilane layers was estimated to be less than 2.2 nm, from the measurement of fluorescence spectra of heteropolysilane LB films having an insulator layer. A single-step energy transfer cannot explain the long migration distance in the PMOdS layer, but the excitons migrate in the wide range of the PMOdS layer by multistep hopping.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluorescence quenching of a monomethin-oxacyanine dye by monomethin thiacyanine was studied in the LB films, and the intermolecular energy transfer between dyes was shown to occur on a scale of 10 nm. The energy transfer distance between the two polysilane layers was estimated to be less than 2.2 nm, from the measurement of fluorescence spectra of heteropolysilane LB films having an insulator layer. A single-step energy transfer cannot explain the long migration distance in the PMOdS layer, but the excitons migrate in the wide range of the PMOdS layer by multistep hopping.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] The energy transfer distance between polysilane layers was examined by employing heteropolysilane Langmuir-Blodgett (LB) films. 15 It was estimated that energy was transferred from a poly(alkylsilane) layer to a poly(arylsilane) layer through an insulator layer thinner than 2.2 nm. The fluorescence spectroscopy of the blends of polysilane was discussed in relation to the miscibility of the blends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence quenching of 2 in the presence of EA1 fitted the Perrin formalism better than the Stern−Volmer fitting, as shown in Figure , and the active sphere volume was calibrated to be 1.63 × 10 11 Å 3 (radius 3400 Å). The value is too large, because perchloropentacyclododecane has been reported to quench the fluorescence of 2 with the v value 10 000 Å 3 (radius 13 Å). , We have reported that photoinduced electron transfers from polysilane LB films to photoexcited TCNQ LB films did not occur over a distance of 50 Å when polyacrylate LB films were incorporated between the polysilane LB film and the TCNQ LB film …”
Section: Resultsmentioning
confidence: 99%
“…34,35 We have reported that photoinduced electron transfers from polysilane LB films to photoexcited TCNQ LB films did not occur over a distance of 50 Å when polyacrylate LB films were incorporated between the polysilane LB film and the TCNQ LB film. 47 Let us presume why EA1 and EA2 show anomalous behavior for fluorescence quenching of polysilane 2, compared with those of other additives previously reported. 34,35 There are a few reports on photosensitizations of peroxides.…”
Section: E*mentioning
confidence: 86%